2019
DOI: 10.1108/ijbm-01-2019-0012
|View full text |Cite
|
Sign up to set email alerts
|

The moderating impact of gender on the acceptance of peer-to-peer mobile payment systems

Abstract: Purpose The purpose of this paper is to determine the significant antecedents of peer-to-peer (P2P) m-payment acceptance and explore the moderating effects of gender on the influence of these predictors with regards to intention of using the system. Design/methodology/approach The research was conducted on a sample comprised of 701 Spanish smartphone users. A multi-group structural equation modeling analysis was used to test the moderating effect of gender with a particular focus on the relationships between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
79
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(88 citation statements)
references
References 64 publications
6
79
1
2
Order By: Relevance
“…In the context of our research, we understand that the usefulness of the payment system will influence intention to use. A body of research, which includes studies focused on mobile banking [16,17] and mobile payments [18][19][20][21][22][23], supports this approach. For all these reasons, the following hypothesis is proposed: Hypothesis 3.…”
Section: User-and Mobile Phone-related Factors: Mobile User Skillfulnmentioning
confidence: 99%
“…In the context of our research, we understand that the usefulness of the payment system will influence intention to use. A body of research, which includes studies focused on mobile banking [16,17] and mobile payments [18][19][20][21][22][23], supports this approach. For all these reasons, the following hypothesis is proposed: Hypothesis 3.…”
Section: User-and Mobile Phone-related Factors: Mobile User Skillfulnmentioning
confidence: 99%
“…In the m-payment context, researchers (e.g., Alaeddin et al, 2018;Kalinic et al, 2019a;Liébana-Cabanillas et al, 2014bMatemba & Li, 2018;Ramos de Luna et al, 2016;Su et al, 2018;Zhao et al, 2019) have used TAM. UTAUT/UTAUT2 were used by other researchers (e.g., Gupta & Arora, 2019;Madan & Yadav, 2016;Oliveira et al, 2016;Shaw, 2015;Wang & Yi, 2012;Widodo et al, 2019).…”
Section: Mobile Payment Adoption Researchmentioning
confidence: 99%
“…Davis, 1989;Pham & Ho, 2015); and (3) it allows for augmentation to incorporate additional variables to capture aspects of adoption and increase its predictive power (e.g. Kalinic et al, 2019a;Liébana-Cabanillas et al, 2019;Phonthanukitithaworn et al, 2016a). Consequently, this study employed the modified version of TAM, as suggested by Venkatesh and Davis (2000), and further extended the model with four additional variables, namely, trust, perceived cost, perceived security, and attractiveness of alternatives.…”
Section: The Conceptual Model and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The results indicated that in Thailand, E-lifestyle significantly moderates the dynamics influencing E-banking predilections of bank customers. (Kalinić et al .,2019) reported that males are most likely to apply mobile banking for payment than females. As a result, they are less impacted by the typical image on user resistance to mobile banking; while in Taiwan, E-lifestyle moderates standard barriers' impact.…”
Section: Lifestylesmentioning
confidence: 99%